Tonic Endocannabinoid Signaling Gates Synaptic Plasticity in Dorsal Raphe Nucleus Serotonin Neurons Through Peroxisome Proliferator-Activated Receptors - Oubraim, Saida; Wang, Ruixiang; Hausknecht, Kathryn A; Shen, Roh-Yu; Haj-Dahmane, Samir (Frontiers in Pharmacology, 2021)
Endocannabinoids (eCBs), which include 2-arachidonoylglycerol (2-AG) and anandamide (AEA) are lipid signaling molecules involved in the regulation of an array of behavioral and physiological functions. Released by postsynaptic neurons, eCBs mediate both phasic and tonic signaling at central synapses. While the roles of phasic eCB signaling in modulating synaptic functions and plasticity are well characterized, very little is known regarding the physiological roles and mechanisms regulating tonic eCB signaling at central synapses. In this study, we show that both 2-AG and AEA are constitutively released in the dorsal raphe nucleus (DRN), where they exert tonic control of glutamatergic synaptic transmission onto serotonin (5-HT) neurons. The magnitude of this tonic eCB signaling is tightly regulated by the overall activity of neuronal network. Thus, short term in vitro neuronal silencing or blockade of excitatory synaptic transmission abolishes tonic eCB signaling in the DRn. Importantly, in addition to controlling basal synaptic transmission, this study reveals that tonic 2-AG, but not AEA signaling, modulates synaptic plasticity. Indeed, short-term increase in tonic 2-AG signaling impairs spike-timing dependent potentiation (tLTP) of glutamate synapses. This tonic 2-AG-mediated homeostatic control of DRN glutamate synapses is not signaled by canonical cannabinoid receptors, but by intracellular peroxisome proliferator-activated receptor gamma (PPARγ). Further examination reveals that 2-AG mediated activation of PPARγ blocks tLTP by inhibiting nitric oxide (NO), soluble guanylate cyclase, and protein kinase G (NO/sGC/PKG) signaling pathway. Collectively, these results unravel novel mechanisms by which tonic 2-AG signaling integrates network activities and controls the synaptic plasticity in the brain.